Optimalisai Mesin Injection Molding Tipe Screw Dengan Produk Klem Pipa Setengah Inci Untuk Mendapatkan Parameter Produksi - Dieta Wahyu Asry Ningtias; Trio Setiyawan; Timotius Anggit kritiawan; Fariz Wisda Nugraha; Mulyono; Muhammad Karel Islam (Journal of Mechanical Engineering and Applied Technology, 2026)
Injection molding is one of the methods used in plastic forming processes. This study aims to optimize the screw-type injection molding machine owned by the Mechanical Engineering Laboratory of xyz, which was previously developed by xyz students. However, the machine had several deficiencies, such as barrel leakage, imperfect feeding in the hopper, unstable heating, and only one mold variation, namely a keychain mold. These issues reduced production efficiency.To overcome these problems, the machine was optimized by replacing and redesigning components such as the screw, barrel, nozzle, transmission system, and by adding a new mold variation for a half-inch pipe clamp. The method involved redesigning and testing based on operational parameters, including feeding temperature, injection temperature, injection time, and cooling time.Testing was conducted by setting the feeding temperature to 220°C, injection temperature between 290°C and 310°C, injection time between 11 and 13 seconds, and cooling time of 15 seconds. The material used was polypropylene (PP). The results showed that the optimal parameters were a feeding temperature of 220°C, injection temperature of 310°C, injection time of 12 seconds, and cooling time of 15 seconds. The resulting product exhibited good quality, with complete filling, no flash, and smooth surface finish. This indicates that the optimized screw-type injection molding machine successfully resolved the previous issues.